PENGARUH PENEMPATAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT MADANG SUKU II OGAN KOMERING ULU TIMUR - Mardani, Mardani; Khoiriah, Siti; Mardeli, Iis; Harlofida, Demsie (Jurnal Signaling, 2024)
The magnitude of the influence of placement and career development on employee performance at the Madang Suku II Ogan Komering Ulu Timur District Office. Based on the results of multiple regression analysis, it was found that placement and career development on employee performance at the Madang Suku II Ogan Komering Ulu Timur District Office was Y = 10,607 - 0.080X1 + 0.631 has been consulted with conservative standards, it is between 0.400- 0.599, which means it is classified as a moderate correlation or influence between placement and career development on employee performance at the Madang Suku II Ogan Komering Ulu Timur District Office. This research was conducted on 12 respondents and after conducting a hypothesis test it was found that the F count = 1.85 and the F table obtained was 4.26, thus the hypothesis proposed could not be accepted. The advice that can be given is that leaders should always pay attention to the needs of their employees at work so that their employees' performance can improve.